STRENGTHENING THE PRINCIPLES OF RELIGIOUS MODERATION TO SUPPRESS RELIGIOUS CONSERVATISM WITH A MULTICULTURALISM APPROACH - Arifin, Syamsul; Rahman, Mufiqur; Haris, Ahmad Burhanuddin; Fuad, Helmi (Jurnal Konseling Pendidikan Islam, 2025)
This research tries to provide an offer in suppressing the issue of religious conservatism through an educational approach. This study uses library research by prioritizing the results of research on religious groups and religious conservatism. The results of this study state that Banks' thinking about multiculturalism can be a principle in strengthening the principles of religious moderation, especially in practical steps of education and learning, how an Islamic educational institution can integrate the principles of religious moderation in a learning curriculum construction in a second educational institution how to build a knowledge process and ensure justice and equality and reduce negative stiga in the life of the nation. The multicultural education approach is very important to be applied in an educational institution, including pesantren, so that this multiculturalism approach can also be carried out in the world of pesantren.